Esoteric Buddhist Theories of Language in Early Kokugaku: The Sōshaku of the Man'yō daishōki - Murphy, Regan E. (Japanese journal of religious studies, 2009)
The early modern renaissance in the study of ancient texts, Kokugaku, has been described as a nativist movement that developed as the antithesis of NeoConfucianism. This paper starts from a different premise. It follows KUGINUKI'S (2007) argument that the introduction of a new framework for the study of the Japanese language by Keichū, the Esoteric Buddhist scholar-monk and "father" of Kokugaku, raised new questions about the ancient Japanese language. Through a close analysis of his discussion of language, this article examines Keichu's explanation of his radical shift in framework, revealing the importance of Esoteric Buddhist ideas in early Kokugaku.